2021
DOI: 10.1177/15459683211062894
|View full text |Cite
|
Sign up to set email alerts
|

Step Number and Aerobic Minute Exercise Prescription and Progression in Stroke: A Roadmap

Abstract: Background While higher therapeutic intensity improves motor recovery after stroke, translating findings from successful studies is challenging without clear exercise intensity targets. We show in the DOSE trial 1 more than double the steps and aerobic minutes within a session can be achieved compared with usual care and translates to improved long-term walking outcomes. Objective We modeled data from this successful higher intensity multi-site RCT to develop targets for prescribing and progressing exercise f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Je nach Fitnesszustand der Patienten soll anschließend mit leichter (<40% HRR) oder moderater Intensität (40–60% HRR) gestartet und das Training über die kommenden Wochen graduell intensiviert werden. Das kontinuierliche Monitoring soll es in Zukunft erlauben, dass die Ausdauer patientenspezifisch optimiert wird und durch die zugeschnittene Trainingsintensität bessere Langzeitergebnisse erzielt werden können 18 . In Kombination mit weiteren Daten, wie z.…”
Section: Sensorisierung In Der Klinikunclassified
“…Je nach Fitnesszustand der Patienten soll anschließend mit leichter (<40% HRR) oder moderater Intensität (40–60% HRR) gestartet und das Training über die kommenden Wochen graduell intensiviert werden. Das kontinuierliche Monitoring soll es in Zukunft erlauben, dass die Ausdauer patientenspezifisch optimiert wird und durch die zugeschnittene Trainingsintensität bessere Langzeitergebnisse erzielt werden können 18 . In Kombination mit weiteren Daten, wie z.…”
Section: Sensorisierung In Der Klinikunclassified
“…However, the effect of these high repetition gait training interventions at aerobic intensities on BP remain unclear. The Determining Optimal Post-Stroke Exercise (DOSE) randomized controlled trial showed evidence of greater improvements in walking recovery among those receiving high repetition gait training at aerobic intensities (i.e., progression to at least 2,000 steps and at least 30 min of 40–60% HRR per session) during inpatient rehabilitation, compared with usual care ( 20 , 23 ). In this secondary analysis, we aimed to determine the effect of high repetition gait training at aerobic intensities on the BP trajectory over the first 12 months post-stroke in participants from the DOSE trial.…”
Section: Introductionmentioning
confidence: 99%